Effects of misonidazole and tetrandrine on production and repair of radiation-induced DNA damage in L7712 cells - Liu Nan; Zheng Xiu-long (Acta Pharmacologica Sinica; Vol 6, No 3 (September 1985): Acta Pharmacologica Sinica, 2016)
Using the modified method of hydroxyapatite centrifugation, we studied the effects of misonidazole(Mis) and tetrandrine (Tet) on the production and repair of DNA single strand breaks(ssb) induced by irradiation in cultured murine L7712 cells. DNA ssb increased linealy with the dose (0-40 Gy) of r-ray irradiation. The production of DNA ssb in the presence of O2 was 3.1 times as that under hypoxia( oxygen enhancement ratio=3.1). Mis selectively increased the production of ssb in cells irradiated in hypoxia (enhancement ratio=2.6 for 10 mM Mis), but had no effect on that of those supplied with O2. Tet did not influence the yields of DNA ssb in either case. The DNA ssb caused by irradiation under hypoxia in the presence of 10 mM Mis was rejoined and the extent of rejoining 120 min after incubation was similar to that with O2. But the kinetics was significantly different. Tet inhibited the rejoining of DNA ssb, no matter when the irradiation was applied. There were only 57% ssb that could be rejoined 120 min after incubation. The inhibition of UDS and DNA synthesis by Tet was also seen.